Comprehensive analysis of area‐specific and time‐dependent changes in gene expression in the motor cortex of macaque monkeys during recovery from spinal cord injury. Issue 7 (6th February 2018) - Higo, Noriyuki; Sato, Akira; Yamamoto, Tatsuya; Oishi, Takao; Nishimura, Yukio; Murata, Yumi; Onoe, Hirotaka; Isa, Tadashi; Kojima, Toshio
Abstract: The present study aimed to assess the molecular bases of cortical compensatory mechanisms following spinal cord injury in primates. To accomplish this, comprehensive changes in gene expression were investigated in the bilateral primary motor cortex (M1), dorsal premotor cortex (PMd), and ventral premotor cortex (PMv) after a unilateral lesion of the lateral corticospinal tract (l‐CST). At 2 weeks after the lesion, a large number of genes exhibited altered expression levels in the contralesional M1, which is directly linked to the lesioned l‐CST. Gene ontology and network analyses indicated that these changes in gene expression are involved in the atrophy and plasticity changes observed in neurons. Orchestrated gene expression changes were present when behavioral recovery was attained 3 months after the lesion, particularly among the bilateral premotor areas, and a large number of these genes are involved in plasticity. Moreover, several genes abundantly expressed in M1 of intact monkeys were upregulated in both the PMd and PMv after the l‐CST lesion. These area‐specific and time‐dependent changes in gene expression may underlie the molecular mechanisms of functional recovery following a lesion of the l‐CST. GRAPHICAL ABSTRACT: Here, we investigated comprehensive changes in gene expression in cortical motor areas after a unilateral lesion of the lateral corticospinal tract (l‐CST). At 2 weeks after the lesion, a large number of genes exhibited altered expression levels in the contralesional primary motor cortex. Orchestrated gene expression changes were present when behavioral recovery was attained 3 months after the lesion. These area‐specific and time‐dependent changes in gene expression may underlie the molecular mechanisms of functional recovery following the l‐CST lesion.